The handler - Woodward, M. P. (Berkley, 2022)
"A disgraced ex-CIA operative must return to the field with only his ex-wife as his handler in this electrifying thriller from a former intelligence officer. A single well-placed American asset has kept Iran's secret uranium enrichment from hitting weapons-grade. For the last decade, a mild-mannered Iranian physicist has enabled a CIA hack into software controlling Iran's gas-centrifuge arrays. But now the saboteur has gone dark, off grid-and he's cut Langley's access until he gets what he wants. Spurred by a tragic accident, the mole has turned the tables, blackmailing his American spymasters. His one demand: an exfil by the only man at CIA he ever trusted-his former handler, John Dale. Without Dale, the asset will expose the hack. Too bad Dale wants nothing to do with CIA. He's barely shaken his rage at Langley, who'd exiled him after an ISIS raid went sideways. Challenging Dale's allegiance, his former bosses had even gone so far as to declare him persona non grata, stripping him of his pension, and worse-his honor. But they need Dale back now, fast. Iranian counterintelligence is closing in. CIA's last firewall against a nuclear terror state is about to crumble. Langley has one final card to play. Senior case officer Meredith Morris-Dale, John's ex-wife, might be able to salvage their shattered bond just enough to recruit Dale for one final mission. An expert handler herself, she'll need to use every trick in the book to get John back in the field. As Meredith and John struggle through their fraught relationship, a craven CIA political hierarchy, Russian interference, and the rogue spy's manipulation, they must reach deep within their shared connection to maintain, recover...or terminate the asset"--